Rent Gaps, Revanchism and Regimes of Accumulation in Mumbai - Whitehead, Judy (Anthropologica, 2022)
This paper examines the spatial reshaping of Mumbai through the lens of rent gaps, showing how differences between actual and potential rents in central regions of the city influenced the decline of the textile industry and working-class neighbourhoods there. It discusses theories of urban rent, changing class relations in Central Mumbai, and situates recent slum clearances within a framework of the new revanchism in global cities. It concludes with a discussion of Mumbai’s projected future as a property and finance-led "island" of accumulation, noting differences between it and Hong Kong and Singapore, cities that are often cited as models of Mumbai’s future redevelopment.